Integrasi Sejarah Lokal Blora Menggunakan Model CTL untuk Meningkatkan Pengetahuan Sejarah Siswa Sekolah Dasar - Intan Setiyaningsih; Kartono Kartono; Suhartono Suhartono (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
Blora has enormous local historical potential. For example, the Hisyudindricus elephant fossil is the only ancient elephant fossil in the world that was found intact in the tropics. Also Kidang caveman fossils, Homo Sapiens from Ngandong, the History of the 5th Sultan of Demak (Duke Aryo Penangsang from Jipang Panolan), Saminism movement, oil history, R.M. Tirto Adhi Suryo (Father of the National Press) and Pramoedya Ananta Toer. The potential of local history has not been conveyed in learning systematically so the benefits of local history as character building, local identity characteristics, pride in the past and awareness of appreciation in students do not grow. Therefore, efforts are made to use the CTL approach to teach local history in sixth-grade elementary school. During the implementation of learning, research was carried out using a quantitative approach. The experimental design used was Post Test Only Control Group Design in the control and experimental classes. The comparison of the averages of the two classes was tested using the "t-test" and the results were that the CTL model was significantly used to integrate local history in sixth-grade elementary school.